Roles of Calcium Signaling in Gene Expression and Photosynthetic Acclimatization of Solanum lycopersicum Micro-Tom (MT) after Mechanical Damage - Campos, Felipe Girotto [UNESP]; Seixas, Diana Pacheco [UNESP]; Barzotto, Gustavo Ribeiro [UNESP]; Jorge, Letícia Galhardo [UNESP]; Ducatti, Karina Renostro [UNESP]; Ferreira, Gisela [UNESP]; Rodrigues, Tatiane Maria [UNESP]; Silva, Edvaldo Aparecido Amaral da [UNESP]; Boaro, Carmen Sílvia Fernandes [UNESP] (MDPI, 2022)
A momentary increase in cytoplasmic Ca2+ generates an oscillation responsible for the activation of proteins, such as calmodulin and kinases, which interact with reactive oxygen species (ROS) for the transmission of a stress signal. This study investigated the influence of variations in calcium concentrations on plant defense signaling and photosynthetic acclimatization after mechanical damage. Solanum lycopersicum Micro-Tom was grown with 0, 2 and 4 mM Ca2+, with and without mechanical damage. The expression of stress genes was evaluated, along with levels of antioxidant enzymes, hydrogen peroxide, lipid peroxidation, histochemistry, photosynthesis and dry mass of organs. The ROS production generated by mechanical damage was further enhanced by calcium-free conditions due to the inactivation of the oxygen evolution complex, contributing to an increase in reactive species. The results indicated that ROS affected mechanical damage signaling because calcium-free plants exhibited high levels of H2O2 and enhanced expression of kinase and RBOH1 genes, necessary conditions for an efficient response to stress. We conclude that the plants without calcium supply recognized mechanical damage but did not survive. The highest expression of the RBOH1 gene and the accumulation of H2O2 in these plants signaled cell death. Plants grown in the presence of calcium showed higher expression of SlCaM2 and control of H2O2 concentration, thus overcoming the stress caused by mechanical damage, with photosynthetic acclimatization and without damage to dry mass production.
Keywords: chlorophyll a fluorescence; gas exchange; hydrogen peroxide; plant stress; RBOH1 genes